HST/COS detection of a Ne viii absorber towards PG 1407+265: an unambiguous tracer of collisionally ionized hot gas?. Issue 3 (27th November 2014) - Hussain, T.; Muzahid, S.; Narayanan, A.; Srianand, R.; Wakker, B. P.; Charlton, J. C.; Pathak, A.
Abstract: We report the detection of Ne viii in a z abs = 0.599 61 absorber towards the QSO PG1407+265 ( z em = 0.94). Besides Ne viii, absorption from H i Lyman series lines (H i  λ1025–λ915), several other low (C ii, N ii, O ii and S ii ), intermediate (C iii, N iii, N iv, O iii, S iv and S v ) and high (S vi, O vi and Ne viii ) ionization metal lines are detected. Disparity in the absorption line kinematics between different ions implies that the absorbing gas comprises of multiple ionization phases. The low and the intermediate ions (except S v ) trace a compact (∼410 pc), metal-rich ( Z  ∼ Z⊙ ) and overdense (log  n H  ∼ −2.6) photoionized region that sustained star formation for a prolonged period. The high ions, Ne viii and O vi, can be explained as arising in a low density (−5.3 ≤ log  n H ≤ −5.0), metal-rich ( Z ≳ Z⊙ ) and diffuse (∼180 kpc) photoionized gas. The S v, S vi and C iv [detected in the Faint Object Spectrograph (FOS) spectrum] require an intermediate photoionization phase with −4.2 < log  n H  < −3.5. Alternatively, a pure collisional ionization model, as used to explain the previous known Ne viii absorbers, with 5.65 < log  T  < 5.72, can reproduce the S vi, O vi and Ne viii column densities simultaneously in a single phase. However, even such models require an intermediate phase to reproduce any observable S v and/or C iv . Therefore, we conclude that when multiple phases are present, the presence of Ne viii is not necessarily an unambiguous indication of collisionally ionized hot gas.